The impact of media utilization on traditional practices, cultural values, and life aspirations of Panay Bukidnon adolescents. - Senalista, Maerell Love Caniel
The study was conducted to asses the impact/influence that media have on the Panay Bukidnon adolescents? traditional practices, cultural values, and life aspirations. Sixteen (16) adolescents served as participants for the study. They are aged from ten (10) to nineteen (19) years old. A semi-structured interview and focused group discussion guide were utilized to capture the intent of the study. Results revealed that participants are Very Aware of their existing traditional practices and cultural values and majority of the participants have reported that media indeed have an impact on their traditional practices, cultural values, and life aspirations. Participants have also disclosed that they want to alleviate themselves and family from poverty and have a sense of stability in general.